Chelation as a strategy to reinforce cationic copper surface protection in acidic solutions. Issue 72 (19th July 2016) - Cai, Liang; Feng, Xue-Qing; Hua, Xin; He, Xiao-Peng; Long, Yi-Tao; Chen, Guo-Rong
Abstract : Surface chelation has been demonstrated to be a promising strategy to address repulsion between protonated corrosion inhibitors and ionized copper surfaces in acids. Abstract : Industrial treatment (such as washing and rescaling) of copper-based equipment with acids requires the use of corrosion inhibitors to mitigate environmental pollution. However, the currently used organic inhibitors for copper, such as benzotriazole (BTA ), are protonated in acidic solutions, thereby weakening the adsorption to a positively charged copper surface. Here we show that the use of an effective copper-ion chelator can overcome the repulsion between protonated inhibitors and a cationic copper surface in acidic solutions. With a variety of surface techniques including time of flight secondary ion mass spectrometry, X-ray photoelectron spectroscopy and X-ray diffraction, we determine that bis-triazolyl indoleamines (BTI s) can strongly coat onto a cationic copper surface in acidic solutions through chelation with Cu(i ) species. The electrochemical techniques used suggest that theBTI s are much better corrosion inhibitors thanBTA, showing consistently an outstanding inhibitive efficiency in spite of the reduction of the inhibitor concentration by 100-fold and the increase of solution temperature and acidic strength. A preliminary cell viability assay suggests that ourBTI is much less toxic thanBTA towards two healthy cell lines.